Modelagem e minimização do consumo de combustível para rotas de coleta de lixo - Reinaldo de Souza Xavier (2010)
The waste collection consists of a vehicle and a set of workers that should collect the demand identified in the edges, considering the existing constraints. The attendance should be made reducing the garbage collecting costs, and such costs refer mainly to the fuel consumption whose nonlinearity characteristic embarrasses the formulation of algoritms that can solve the problem. The purpose of this work is to present a solution to the fuel consumption minimization,using linear programming model joined with heuristic methods. The model isauthenticated in a set of problems during the development of the model and after that it is tested in the garbage collection in one urban district of Montes Claros - Minas Gerais, allowing a comparison between both of the values. It was perceived a reduction of 5% in the fuel consumption when both of the cases are compared. This percentage is expressive, considering that urban cleanness services are responsible for 15% of the costs of the municipality